Filósofos en 90 minutos. (Pack 4), (Sócrates, Confucio, Aristóteles, Tomás de Aquino, San Agustín y Platón) - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2017)
The Pack Filósofos 4 collection brings together 6 of the most outstanding philosophers of Antiquity and the Middle Ages.
Sócrates en 90 minutos -- Confucio en 90 minutos -- Aristóteles en 90 minutos -- Tomás de Aquino en 90 minutos -- San Agustín en 90 minutos -- Platón en 90 minutos.
This collection of books by Strathern were published separately in print. The publisher now combined them by subject and published them together in digital format.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed February 7, 2019)
Keywords: Socrates; Confucius; Aristotle; Thomas, -- Aquinas, Saint, -- 1225?-1274.; Augustine, -- of Hippo, Saint, -- 354-430.; Plato; Philosophers, Ancient -- Biography; Philosophers, Medieval -- Biography; Biographies; Electronic books